What is Extreme Southern Bahia in the 21st century in times of globalization? - CERQUEIRA NETO, Sebastião Pinheiro Gonçalves de; Silva, Leonardo Thompson da (Geografares, 2016)
The formation of new Brazilian States is a topic that is far from being a scholarly unanimity, however, geography cannot and should not hide this debate. The great territorial dimension of some States and government inefficiency have become obstacles to regional integration. The hierarchy of places and globalization are components that exert strong influence on the process of fragmentation of the territories. The reflection that I present in this article is part of the result of my doctoral thesis about the geographical dynamics of the extreme south of Bahia. Of course we cannot standardize State dynamics, but realizes that it is increasingly difficult for some federal units keep their regions within a management model that is highly exclusionary and concentrator.Keywords: Bahia, Regional Integration, Fragmentation.